2021
DOI: 10.1029/2021ja029254
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Evolution of Wave‐Particle Interaction Region Deduced From Flash‐Type Auroras and Chorus‐Ray Tracing

Abstract: Cyclotron resonant wave-particle interactions are of fundamental importance as ubiquitous drivers of particle heating, acceleration, and precipitation throughout supernova remnants (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Typical pulsating auroras show quasi‐periodic luminous modulations related to a bundle of chorus elements (Kasahara et al., 2018; Miyoshi et al., 2010; Nishimura et al., 2020), but flash aurora shows a transient luminous response related to an isolated chorus element. The typical duration and patchy size of flash auroras are less than 1 s and less than 4,000 km 2 , respectively (Ozaki et al., 2021). Kataoka et al.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Typical pulsating auroras show quasi‐periodic luminous modulations related to a bundle of chorus elements (Kasahara et al., 2018; Miyoshi et al., 2010; Nishimura et al., 2020), but flash aurora shows a transient luminous response related to an isolated chorus element. The typical duration and patchy size of flash auroras are less than 1 s and less than 4,000 km 2 , respectively (Ozaki et al., 2021). Kataoka et al.…”
Section: Methodsmentioning
confidence: 99%
“…Typical pulsating auroras show quasi-periodic luminous modulations related to a bundle of chorus elements (Kasahara et al, 2018;Miyoshi et al, 2010;Nishimura et al, 2020), but flash aurora shows a transient luminous response related to an isolated chorus element. The typical duration and patchy size of flash auroras are less than 1 s and less than 4,000 km 2 , respectively (Ozaki et al, 2021). Kataoka et al (2012) reported a rapid 54-Hz modulation in a standard periodic pulsating auroral event, but such rapid luminous modulations are different from the transient luminous emission of the isolated flash aurora.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations